Effects of preterm birth on HIV acquisition risk and antiretroviral prophylaxis safety in HIV-exposed Infants in Botswana - Ajibola, Gbolahan (Department of Public Health and Family Medicine, 2024)
Background: The risk of in-utero and peripartum HIV acquisition in HIV-exposed infants born prior to 37 weeks completed gestational age (preterm), is thought to be high when compared with those delivered at term. However, limited data exist on the differential risk of HIV acquisition among infants born preterm following foetal exposure to HIV versus those born at term. With a reported increase in the prevalence of preterm delivery among infants with in-utero HIV and antiretroviral (ARV) drug exposure, it is pertinent to understand the risks associated with mother-to-child-transmission (MTCT) of HIV in infants born preterm versus those born on or after 37 weeks gestational age, as a means of identifying opportunities to eliminate MTCT (eMTCT). Furthermore, Botswana's current Prevention of Mother-to-Child Transmission of HIV (PMTCT) guidelines recommend a variety of ARV prophylaxis strategies in the first 4 – 6 weeks of life for HIV-exposed infants depending on their risk for HIV acquisition, which ranges from triple antiretroviral (ARV) prophylaxis for infants deemed to be at “high risk” for HIV-acquisition to twice-daily dosing of zidovudine for the first 4-6 weeks of life for infants deemed to have a low HIV acquisition risk. At the time of the MPEPU study (2010 – 2015), Botswana offered 4 weeks of zidovudine (ZDV) alone as post-exposure prophylaxis to all exposed infants, however, participants enrolled in the study were given the option to receive once daily Nevirapine (NVP) as prophylaxis if randomized to a breastfeeding arm for the entire duration of breastfeeding in the absence of maternal 3-drug ART. Equally important to understanding the risk of HIV acquisition among infants born preterm is an understanding of the hematologic safety of ARV prophylaxis strategies. Methods: Using data extracted from a Botswana-based placebo-controlled trial evaluating the effect of co-trimoxazole (CTX) on mortality in infants who were HIV-exposed in-utero (the Mpepu Study), we describe the prevalence, timing, and risk factors for HIV acquisition in infants born preterm versus those born at term and assessed the hematologic safety of ARV prophylaxis among HIV-exposed preterm infants in the first month of life. Fisher's exact tests were used to compare the prevalence and timing of infants seroconverting at birth or within 72 hours post-delivery (for in-utero estimates) and those testing positive at 14-34 days after an initial negative result at birth (for peripartum estimates), with prevalence ratios (PR) calculated to ascertain the magnitude and direction of observed associations. The same approach was used to compare the occurrence of severe anaemia and neutropenia between full-term and preterm infants based on ARV prophylaxis received. A multivariable logistic regression model was fit to identify risk factors for HIV acquisition and severe hematologic effects of ARV prophylaxis in the first month of life. Results: Two thousand eight hundred and sixty-six Mpepu infants, all with in-utero HIV exposure, were included in this secondary analysis. Of these, 532 (19%) were born preterm and 2334 (81%) were born at term. There was no significant difference in HIV acquisition rate between preterm and term infants overall (0.8% versus 0.6%, p=0.54, PR=1.33), at birth (0.2% versus 0.3%, p=1.00, PR=0.67) or at 14-34 days post-delivery (0.6% versus 0.3%, p=0.41, PR=2). The only significant predictor of HIV acquisition in both preterm and term infants was associated with the mother's ARV drug regimen as either treatment or prophylaxis. Triple-drug antiretroviral treatment (ART) use in women living with HIV (WLHIV) during the index pregnancy was associated with an observed decrease in odds of HIV acquisition in both preterm and term infants compared to infants born to women who received ZDV only or no ARV prophylaxis at all in the index pregnancy [adjusted Odds Ratio (aOR): 0.003; 95% Confidence Interval (CI): 0.001 – 0.02, p<0.001]. Of a total of 2746 children with haemoglobin results, 23 (0.8%), [10 preterms versus 13 born full term] infants had severe anaemia in the first month of life, while 43 (1.5%) [29 preterms versus 14 full terms] of 2733 children had severe neutropenia. Of 1524 neonates who received twice daily ZDV as prophylaxis, 17 (1.1%) [7 preterms versus 10 full term] had severe anaemia compared to 6 (0.5%) [3 preterms versus 3 full terms] of 1222 neonates who received oncedaily dosing of NVP. Twenty-eight 91.8%) [8 preterms versus 20 full term] of 1518 neonates who received twice daily ZDV as prophylaxis and 15 (1.2%) [4 preterms versus 11 full terms] of 1215 neonates who received once-daily dosing of NVP had severe neutropenia. A significantly higher proportion of preterm infants had severe anaemia when compared with those delivered at term (1.9% versus 0.6%, p=0.005, PR=3.16). A similar trend was observed with neutropenia, with a higher proportion of preterm infants with severe neutropenia when compared to term infants (2.5% versus 1.3%, p= 0.070, PR=1.92). Infants with severe anaemia were more likely to have been born preterm (aOR: 2.41; 95% C.I: 0.96 – 6.03; p=0.05) while those with severe neutropenia were more likely to have formula-fed at birth (aOR: 0.37; 95% C.I: 0.19 – 0.73; p=0.004) and younger (14-27 days) at the time of testing (aOR: 0.09; 95% C.I: 0.03 – 0.33; p=<0.001). Infant ARV prophylaxis (twice daily ZDV versus once daily NVP) and randomized treatment arm (CTX versus placebo) did not significantly contribute to the occurrence of severe anaemia and neutropenia. Conclusions: In settings with low MTCT rates attributable to widespread use of maternal ART in pregnancy, as in Botswana, infants born preterm experienced similar rates of HIV acquisition compared to those delivered at term. Reassuringly, ART use by women in pregnancy significantly reduces the risk of infant HIV acquisition. Infant post-exposure ARV prophylaxis (twice daily ZDV versus once daily NVP) appeared safe in both preterm and term infants and did not contribute to the slight increase in cases of severe hematologic adverse events observed in preterm. However, in an era where triple ARV prophylaxis is now recommended for infants at high risk of HIV acquisition, understanding the hematologic safety of this approach among preterm infants is of paramount importance.